2017
DOI: 10.1186/s12890-017-0459-6
|View full text |Cite
|
Sign up to set email alerts
|

FEV1 and FVC and systemic inflammation in a spinal cord injury cohort

Abstract: BackgroundSystemic inflammation has been associated with reduced pulmonary function in individuals with and without chronic medical conditions. Individuals with chronic spinal cord injury (SCI) have clinical characteristics that promote systemic inflammation and also have reduced pulmonary function. We sought to assess the associations between biomarkers of systemic inflammation with pulmonary function in a chronic SCI cohort, adjusting for other potential confounding factors.MethodsParticipants (n = 311) prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…19 Adiponectin has antioxidant and anti-inflammatory properties, 6 and systemic inflammation has been shown to be inversely associated with lung function in humans. [46][47][48] These previous work supports our findings that increasing cord blood adiponectin within the range of concentrations observed in this study (2.15-142.57 μg/ml) may be associated with increased lung function in early childhood. Furthermore, these prior findings also supported our observation that adjustment with child serum cotinine as a marker for secondhand smoke exposure attenuated the positive association between cord serum adiponectin and %FEV in girls, because secondhand smoke is associated with lung inflammation and function.…”
Section: Discussionsupporting
confidence: 90%
“…19 Adiponectin has antioxidant and anti-inflammatory properties, 6 and systemic inflammation has been shown to be inversely associated with lung function in humans. [46][47][48] These previous work supports our findings that increasing cord blood adiponectin within the range of concentrations observed in this study (2.15-142.57 μg/ml) may be associated with increased lung function in early childhood. Furthermore, these prior findings also supported our observation that adjustment with child serum cotinine as a marker for secondhand smoke exposure attenuated the positive association between cord serum adiponectin and %FEV in girls, because secondhand smoke is associated with lung inflammation and function.…”
Section: Discussionsupporting
confidence: 90%
“…A possible hypothesis can be that impaired lung function leads to a systemic inflammation with elevated CRP level which induces NETosis. Presently, however, there is a controversy in the scientific literature whether increased systemic inflammation leads to impaired lung function or inversely 24 . It also requires further studies, whether this elevated NET level contributes to the impaired lung function or to the disease pathogenesis creating a vicious circle.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing or maintenance of PF parameters has crucial meanings for many patients with SCI. Hart et al [ 40 ] has reported that lower FEV 1 and FVC associate with higher inflammatory factors that reflect systemic inflammation. Hence, better results of FEV 1 and FVC are beneficial to reduce systemic inflammation and manifested better functions of principal bronchus.…”
Section: Discussionmentioning
confidence: 99%